Investigating adolescent psychological wellbeing in an educational context using PISA 2018 Canadian data - Liu, Yan; Maltais, Natasha S.; Milner-Bolotin, Marina; Chachashvili-Bolotin, Svetlana (Frontiers in Psychology, 2024)
Adolescent psychological well-being has been identified as an important public health priority and one of the major challenges facing young people. However, few studies have examined Canadian adolescent well-being nationwide in the past decade and even fewer studies have examined this issue for immigrant adolescents. This study aims to investigate Canadian adolescent psychological well-being (PWB) via nationally representative data from the Programme for International Student Assessment (PISA) 2018. We explored what social and educational factors were critical in predicting Canadian adolescents' PWB, how adolescents from immigrant families differed from their non-immigrant peers in their well-being, and how adolescents' PWB was related to their academic performance. Mixed effects modeling was adopted for data analysis. Our results showed that various social and educational factors were associated with adolescent PWB, but these relationships varied depending on which aspect of PWB was examined. Immigrant adolescents were shown to have higher levels of PWB when student attitudes towards immigrants were more positive. Additionally, most aspects of PWB were important for achievement performance. Our findings on the well-being of Canadian adolescents could offer valuable insights for other countries with diverse populations, especially those with immigrants.